Determinants of Out-of-Network Utilization of Care Among Insured Clients Under the National Health Insurance Fund of Sudan - Elhadi YAM; Zaghloul AAZ; El Dabbah NA (Risk Management and Healthcare Policy, 2022)
Yasir Ahmed Mohammed Elhadi, Ashraf Ahmed Zaher Zaghloul, Noha Ahmed El Dabbah Department of Health Administration and Behavioral Sciences, High Institute of Public Health, Alexandria University, Alexandria, EgyptCorrespondence: Yasir Ahmed Mohammed Elhadi, Department of Health Administration and Behavioral Sciences, High Institute of Public Health, Alexandria University, 165 El Horrya Avenue, Alexandria, Egypt, Tel +20 1556494566, Email hiph.yelhadi@alexu.edu.egPurpose: Knowledge of insured clients’ utilization behavior is essential for developing evidence-based interventions for reform activities. This study explored the magnitude and determinants of voluntary out-of-network physician visit utilization among an insured population under the National Health Insurance Fund (NHIF) of Sudan.Methods: This study was a cross-sectional survey conducted at the primary healthcare centers of NHIF in Al Jazirah state in Sudan. A structured interview questionnaire was used to collect data related to socio-economic and health insurance characteristics of NHIF clients and to assess their utilization behavior. Data were collected from September to October 2021.Results: Of 768 NHIF clients who were interviewed (mean age 46 years, 55.1% females), 63.2% reported using out-of-network physician visits during the last six months prior to the interview. The median out-of-pocket payment for the last out-of-network physician visit was 5000 Sudanese pounds. The regression analysis revealed that clients’ gender, marital status, self-reported health, overall rating of the quality of care, rating of the general practitioner care, and ease of referral to a specialist were the significant determinants for seeking out-of-network physician care.Conclusion: A high magnitude of out-of-network physician visit utilization was found among the insured NHIF clients of Al Jazirah state in Sudan. Policymakers should address issues identified in the current study to reduce patients’ leakage to out-of-network services.Keywords: out-of-network, physician visit, health insurance, healthcare utilization, Sudan